2011
DOI: 10.1254/jphs.10209fp
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ca2+-Release–Activated Ca2+ Channel (CRAC) and K+ Channels by Curcumin in Jurkat-T Cells

Abstract: Abstract. The increase in cytoplasmic Ca] c of Jurkat-T cells using the patch clamp technique and fura-2 spectrofluorimetry. Curcumin (10 μM) inhibited store-operated Ca 2+ entry (SOCE). Consistently, dose-dependent inhibition of I CRAC by curcumin was confirmed in Jurkat-T (IC 50 , 5.9 μM) and the HEK293 cells overexpressing Orai1 and STIM1 (IC 50 , 0.6 μM). Also, curcumin inhibited both I Kv (IC 50 , 11.9 μM) and I SK4 (IC 50 , 4.2 μM). The other polyphenols (rosmarinic acid, resveratrol, and epigallocatechi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Curcumin may also induce antiinflammatory action via inhibition of Ca 2+ -releaseactivated Ca 2+ channels and K + channels in lymphocytes when it is orally administered (95). However, considering the limited pharmacokinetic availability of orally taken curcumin, careful interpretation is required for determining the effects in vivo (95). Recent studies suggest the possibility that a,b-unsaturated carbonyl based compounds might serve as the leading molecules for the design and development of improved antiinflammatory agents (96).…”
Section: Anti-inflammatory Activity In Human Gingivitis Modelmentioning
confidence: 99%
“…Curcumin may also induce antiinflammatory action via inhibition of Ca 2+ -releaseactivated Ca 2+ channels and K + channels in lymphocytes when it is orally administered (95). However, considering the limited pharmacokinetic availability of orally taken curcumin, careful interpretation is required for determining the effects in vivo (95). Recent studies suggest the possibility that a,b-unsaturated carbonyl based compounds might serve as the leading molecules for the design and development of improved antiinflammatory agents (96).…”
Section: Anti-inflammatory Activity In Human Gingivitis Modelmentioning
confidence: 99%
“…Pretreatment with cyanidin-3-glucoside (15 µg/ml) for 30 min significantly inhibited the thapsigargin-induced SOCE responses by 57.8% and the ATP-induced responses by 88.0%. It has been reported that curcumin, a non-flavonoid polyphenol [23], inhibits SOCE in Jukat-T cells [24]. …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, when stimulated by ConA, a sluggish increase in [Ca 2+ ] c was observed in the presence of Gd 3+ , and the Gd 3+ -resistant Ca 2+ influx was inhibited by 30 μM 2-APB. αCD3-induced Δ[Ca 2+ ] c was previously shown to be completely inhibited by 2-APB at above 30 μM [22,29]. The summaries of [Ca 2+ ] c at initial peak and at 400 s from the agonist application are shown as bar graphs.…”
Section: Resultsmentioning
confidence: 99%